2020
DOI: 10.3389/fmicb.2020.566691
|View full text |Cite
|
Sign up to set email alerts
|

Iron Uptake Mechanisms in Marine Phytoplankton

Abstract: Oceanic phytoplankton species have highly efficient mechanisms of iron acquisition, as they can take up iron from environments in which it is present at subnanomolar concentrations. In eukaryotes, three main models were proposed for iron transport into the cells by first studying the kinetics of iron uptake in different algal species and then, more recently, by using modern biological techniques on the model diatom Phaeodactylum tricornutum. In the first model, the rate of uptake is dependent on the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 106 publications
1
37
0
1
Order By: Relevance
“…Notably, the iron enrichment-induced downregulation of these recently discovered major players in iron uptake was also detected in all species of our coculture model. Both phytotransferrin-mediated and siderophore-bound iron uptake mechanisms are most likely based on elaborate machinery involving endocytosis [35] ; thus, this adaptation to life under iron-limited conditions requires complex fine-tuning.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the iron enrichment-induced downregulation of these recently discovered major players in iron uptake was also detected in all species of our coculture model. Both phytotransferrin-mediated and siderophore-bound iron uptake mechanisms are most likely based on elaborate machinery involving endocytosis [35] ; thus, this adaptation to life under iron-limited conditions requires complex fine-tuning.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrient limiting the growth of siderophore producers could then possibly limit bioavailable iron delivery to the whole community, contributing to CIC. The details matter here though, as this siderophore-bound iron is not available to all community members equally ( Hutchins et al, 1999 ; Sanchez et al, 2018 ; Sutak et al, 2020 ). Identifying microbial groups that rely on interactions to obtain BPNs will be important for investigations of additional mechanisms of CIC.…”
Section: Cases Of Community Interaction Co-limitationmentioning
confidence: 99%
“…Combining these two iron uptake models and DrFe content in Sishili Bay, the relative stability of DrFe may be due to the following reason: weak chelated iron and unchelated inorganic iron could be first consumed, and complexed iron might be converted into DrFe by photoreduction and/or cell surface reduction in time to maintain the normal growth of phytoplankton [44]. Phytoplankton indeed can access Fe from strong organic ligands, such as siderophores excreted by the cells or produced by other bacterial or fungal species, through direct metal exchange accomplished by the ternary complex formed by iron chelator and acceptor [62]; but as long as DrFe concentrations are high enough, which is the case in this study as confirmed in Section 4.6 below, the consumption of Fe from strong ligands will be negligible [63]. Even so, the Fe(II)s model is the dominant but not the only iron uptake mechanism in this study, as several studies have strongly suggested that no one model can account for all iron uptake, with several different iron uptake mechanisms coexisting in a single species [62,64].…”
Section: Temporal Distribution Characteristics Of Drfementioning
confidence: 99%
“…Phytoplankton indeed can access Fe from strong organic ligands, such as siderophores excreted by the cells or produced by other bacterial or fungal species, through direct metal exchange accomplished by the ternary complex formed by iron chelator and acceptor [62]; but as long as DrFe concentrations are high enough, which is the case in this study as confirmed in Section 4.6 below, the consumption of Fe from strong ligands will be negligible [63]. Even so, the Fe(II)s model is the dominant but not the only iron uptake mechanism in this study, as several studies have strongly suggested that no one model can account for all iron uptake, with several different iron uptake mechanisms coexisting in a single species [62,64].…”
Section: Temporal Distribution Characteristics Of Drfementioning
confidence: 99%